Cross-Countries Comparison Toward Digital Currency Acceptance: Integrating UTAUT2 Into ITM - Lin, Xin; Zhang, Qiuxiang; Jong, Din (Frontiers in Psychology, 2022)
In the context of digital monetary market integration, the importance of cross-border digital currency research is receiving prominent attention. This study integrated extended Unified Theory of Acceptance and Use of Technology (UTAUT2) and initial trust factors (ITM) into an integrative framework, which synthetically complemented the objective measures and subjective insight of digital currencies. The results indicated that the integrated framework which verified its robustness predicting the acceptance and recommendation intention of digital currency. By analyzing the two different digital currencies’ features, this research puts forward a set of targeted solutions to ensure that Chinese and Korean digital currencies’ users make a long-term policy for the sustainability, eventually benefit the cross-border digital monetary transactions and economic cooperation in Asia, which lead the world to the sustainable development in the digital currencies field.